Association between the atherogenic index of plasma, body mass index, and cardiovascular diseases in Chinese middle and old-aged adults: a mediation analysis - Xu, Yirui; Liu, Mengping; Yang, Wenbo; Zhang, Wenjiao; Fan, Heze; Xu, Yu; Zhou, Juan; Yuan, Zuyi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundEvidence has emerged that suggests the atherogenic index of plasma (AIP), as determined by blood lipid levels, is a valuable predictor of the onset of cardiovascular diseases. The correlation between AIP and cardiovascular diseases may be facilitated by body mass index (BMI), as atherosclerosis is prevalent in overweight and obese populations. In order to assess the combined predictive value of the AIP and BMI in predicting outcomes associated with cardiovascular diseases, this study sought to determine if BMI mediates the relationship between the AIP and cardiovascular disease risk.MethodsParticipants in this study were those who were without cardiovascular diseases at baseline and were members of the China Health and Retirement Longitudinal Study (CHARLS). We performed adjusted regression analysis and mediation. AIP was calculated using the logarithm of the ratio of triglycerides (TG) to high-density lipoprotein cholesterol (HDL-C). The estimated body weight and height were used to calculate the BMI.ResultsThis study included 5468 participants. Cardiovascular diseases were highly linked with both BMI and AIP. In contrast to those with a lower AIP (median level) and BMI <24, those with an elevated AIP and increased BMI presented a higher risk for developing cardiovascular conditions (HR: 1.789; 95% CI: 1.491–2.147). Additionally, about 30.57% of the connection between AIP and cardiovascular diseases was strongly mediated by BMI.ConclusionsAmong Chinese adults in their middle and advanced years, the AIP and BMI jointly have been associated to a higher risk of cardiovascular diseases, and BMI could serve as a mediator in this connection.